COVID-19 Symptomatic Newborns with Possible Postpartum Transmission of SARS-CoV-2 - Mohammad Hosein Ataee Nakhaei; Sahar Safapour Moghadam; Saeedeh Yaghoubi (Hindawi Limited, 2022)
Coronavirus disease 2019 (COVID-19) infection, which was initially reported in Wuhan, China, in December 2019, had a rapid spread throughout the world becoming a new global crisis. Today, very little is known about neonatal COVID-19 infection. Herein, we tried to define the clinical and demographic characteristics, risk factors, and laboratory and imagining findings of neonates who tested positive for COVID-19 and were admitted to the NICU (neonatal intensive care unit) of Ali Ibn Abi Taleb Hospital, Zahedan, Iran, from June 2021 to July 2021. All full-term and premature neonates diagnosed with COVID-19 were included in the study. Their ages ranged from 1 to 21 days at admission, including 6 boys and 4 girls. The medical records of mother-baby dyads were reviewed. All mothers, except for one, were negative for COVID-19 infection. The most frequent findings in the neonates were fever, poor feeding, respiratory distress, cough, hypoxemia, and drooling. Broad-spectrum antibiotics were administered as routine. All neonates, except for one, needed respiratory support, and intratracheal surfactant was administered for three newborns. Three neonates with severe disorders died during the study period.